Clinical and Radiological Report of a Soft Shell in a Tortoise (Testudo graeca) - Sahar Etemadi; Seyed Mohammad Hashemi-Asl; Alaleh Rakhshanpour (Iranian Journal of Veterinary Surgery, 2023)
There are different types of metabolic bone diseases, and nutritional secondary hyperparathyroidism, or nutritional metabolic bone disease, is the most common one in turtles. This disease may cause deformities and paralysis of the posterior limb. In this article, we describe a tortoise (Testudo gareca) with soft shell syndrome and cloacal inflammation. A 1.5-year-old tortoise weighing 600 grams was referred to the faculty clinic for anorexia and inability to defecate. During the clinical examination, the shell was observed to be curvy and excessively soft when touched, along with swelling around the cloaca. Lateral and dorsal-ventral radiographs were performed to further evaluate the patient. This clinical report presents the clinical findings and radiographic profile of a soft shell in a tortoise.